Capital nationality and economic development - Guilherme Klein Martins (University of Massachusetts, Department of Economics, 2022)
This paper reviews different literature strands and performs an empirical test to evaluate how capital ownership, particularly its nationality, might affect long-run economic develop- ment. Our results indicate that low and middle-income countries with larger foreign capital stock in 1980 had lower economic growth over the next 39 years. The estimations also indi- cate that these economies developed a less specialized export basket, which became relatively more concentrated in low-tech goods. The results are inverted to high-income economies, for which the effects are positive on GDP growth and export specialization and complexi- fication. The results are in line with the evidence that countries can benefit from foreign investment only if they have sufficiently developed 'absorptive capabilities' (e.g., financial markets and human capital). The results can also be interpreted in light of theoretical and empirical evidence that foreign capital might reinforce static comparative advantages in developing economies, particularly in middle-income ones.
Keywords: O14; F43; F23; 330; capital ownership; development; FDI; specialization